2023
DOI: 10.1007/s00590-023-03712-w
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between anthropometric measurements and graft size in anterior cruciate ligament reconstruction: a systematic review and meta-analysis

Loay A. Salman,
Isam Sami Moghamis,
Ashraf T. Hatnouly
et al.

Abstract: Purpose This systematic review and meta-analysis aimed to investigate the correlation between anthropometric measurements and graft size in anterior cruciate ligament (ACL) reconstruction. Methods A systematic search of Ovid MEDLINE, Embase, and Cochrane Library databases was conducted for observational studies published until March 2023 that reported the relationship between anthropometric data [height, weight, body mass index (BMI), age, gender, thigh le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
(38 reference statements)
1
2
0
Order By: Relevance
“…A study done by Salman et al [13] showed that height, weight, thigh length and circumference all demonstrated a moderately positive correlation with graft size within this review. Such anthropomorphic measurements can be considered surrogate markers for muscular development, both in relation to cross-sectional area and axial muscular length and thus can be considered more relevant markers to base potential graft size upon.…”
Section: Discussionsupporting
confidence: 62%
“…A study done by Salman et al [13] showed that height, weight, thigh length and circumference all demonstrated a moderately positive correlation with graft size within this review. Such anthropomorphic measurements can be considered surrogate markers for muscular development, both in relation to cross-sectional area and axial muscular length and thus can be considered more relevant markers to base potential graft size upon.…”
Section: Discussionsupporting
confidence: 62%
“…However, the findings from this review also suggest that anthropometric characteristics may not be as strong as MRI in predicting graft diameter. It has been proposed that anthropometric characteristics, specifically weight and height, could serve as surrogate markers of muscle development [52], thus leading to greater graft diameters. Cutoffs for height and weight with an associated sensitivity and specificity for predicting graft diameter above 8 mm were not widely reported from study to study.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies thereafter have found correlations between magnetic resonance imaging (MRI) evaluation of tendon cross-sectional area (CSA) and graft diameter, advocating for its utility in providing surgeons with a tool for predicting graft size [9,49,62]. Other studies have found significant correlations between anthropometric characteristics, such as height, weight and body mass index (BMI), with graft diameter [6,41,52]. Hence, some have advocated for using both radiographic and demographic parameters for preoperative planning [24,41].…”
Section: Introductionmentioning
confidence: 99%